2011
DOI: 10.1590/s0102-05362011000300024
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization on intercropping of lettuce and rocket

Abstract: The work was carried out at UNESP, Jaboticabal, São Paulo State, Brazil, from September to December 2006, to evaluate the effect of nitrogen fertilization on intercropping of lettuce and rocket. The experiment was conducted in a randomized complete block design, with four replications, treatments being arranged in a 4 x 4 + 2 factorial design. The treatments were the result of a combination of four N rates for lettuce (0, 65, 130 and 195 kg ha -1 ) and four N rates for rocket (0, 65, 130 and 195 kg ha -1 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…These authors also found no differences in fresh mass between sole cropping (475.8 g m -1 ) and intercropping (440.5 g m -1 ) in the spring, regardless of the time of the sowing of the rocket relative to the transplantation of crinkly lettuce. Similarly, Barros Júnior et al [ 12 ] found no difference in fresh mass between sole cropping and intercropping with crisp lettuce in the spring.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These authors also found no differences in fresh mass between sole cropping (475.8 g m -1 ) and intercropping (440.5 g m -1 ) in the spring, regardless of the time of the sowing of the rocket relative to the transplantation of crinkly lettuce. Similarly, Barros Júnior et al [ 12 ] found no difference in fresh mass between sole cropping and intercropping with crisp lettuce in the spring.…”
Section: Resultsmentioning
confidence: 93%
“…Barros Júnior et al [ 12 ] also reported a higher fresh mass of lettuce in a sole crop than in an intercrop with rocket in the spring. Barbosa et al [ 14 ] reported that fresh mass was higher with intercropping (crisp lettuce and rocket) than sole cropping in the autumn but not winter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018), Bezerra Neto et al (2012), and Oliveira et al (2010). However, due to a lack of knowledge regarding the nitrogen (N) requirement for both crops, a factor modified by the coexistence of species (BARROS JÚNIOR et al, 2011), the fertilization concentration used for intercropping is empirically based on the recommended nutrient doses for monocrops.…”
Section: Introductionmentioning
confidence: 99%
“…There are several vegetables combinations that can be used in intercropping, with the lettuce being a crop frequently used (COSTA et al, 2007;REZENDE et al, 2011;MOTA et al, 2012;CECÍLIO FILHO et al, 2013;CECÍLIO FILHO et al, 2015). Among the leafy vegetables, rocket is a crop that can be used as an intercrop, due to its erect growth and high marketing price, presenting a great combination with lettuce (BARROS JÚNIOR et al, 2011;OLIVEIRA et al, 2010;BARBOSA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%